Spectrophotometric Indirect Determination of Captopril through Redox Reaction with n-bromosuccinimide and RB dye in Pharmaceutical Products - Kokhasmail, Dashne M.; Tahir, Tara F.; Azeez, Kurdistan F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
A simple, accurate, and sensitive method for the spectrophotometric determination of captopril in bulk and dosage forms is reported. The method is based on the bromination of captopril with excess solution of n-bromosuccinimide (NBS) in HCl acid medium. The excess NBS is pursued by the assessment of the residual NBS based on its ability to bleach the rhodamine B dye and measuring the absorbance at 555 nm. The amount of NBS reacted coincides to the drug content. The different experimental parameters influencing the development and stability of the color are precisely studied and optimized. Beer’s law is valid within a concentration range of 0.3–1.0 μg/mL with a correlation coefficient R2 = 0.991. The limit of detection 0.169 μg/mL is attained and relative standard deviation values for five replicated measurements of 0.3, 0.7, and 1.0 μg/mL captopril were between 0.53% and 2.03%. No interference is detected from prevalent additives found in pharmaceutical preparations. The proposed method is profitably put on to the determination of captopril in the tablet formulations with mean recoveries 98.91–101.27% and the results were statistically confronted with those of a reference method by applying Student’s t-and F-test.